Sex Trade and ‘Floating Migration’ in the Colombian Armed Conflict - Laverde Rodriguez, Carlos Alfonso (Anti-Trafficking Review, 2024)
This article analyses the dynamics of the sex trade in the context of the Colombian armed conflict. It argues that the sex trade has adapted to the conflict and its different actors and demonstrates how it operates in such constrained contexts. The article is based on ethnographic research with sex workers in Bogotá who have experience working in different conflict zones. It found that the sex trade is dynamic and that sex workers develop strategies to resist violence and adapt to the respective contexts. These sex workers are a type of ‘floating migrants’, living and surviving on the sex trade not only for the income it generates but also for the relationships they build with other sex workers, establishment managers, and combatants. The article concludes that the sex trade in Colombia did not arise as a result of the armed conflict. Rather, it is a phenomenon that exists as part of a broader market before, during, and after episodes of violence.